Validation and cross‐linguistic adaptation of the Frenchay Dysarthria Assessment (FDA‐2) speech intelligibility tests: Hebrew version. Issue 5 (17th June 2022) - Icht, Michal; Bergerzon‐Bitton, Orly; Ben‐David, Boaz M.
Abstract: 'Dysarthria' is a group of motor speech disorders resulting from a disturbance in neuromuscular control. Most individuals with dysarthria cope with communicative restrictions due to speech impairments and reduced intelligibility. Thus, language‐sensitive measurements of intelligibility are important in dysarthria neurological assessment. The Frenchay Dysarthria Assessment, 2nd edition (FDA‐2), is a validated tool for the identification of the nature and patterns of oro‐motor movements associated with different types of dysarthria. The current study conducted a careful culture‐ and linguistic‐sensitive adaption of the two intelligibility subtests of the FDA‐2 to Hebrew (words and sentences) and performed a preliminary validation with relevant clinical populations. First, sets of Hebrew words and sentences were constructed, based on the criteria defined in FDA‐2, as well as on several other factors that may affect performance: emotional valence, arousal and familiarity. Second, the new subtests were validated in healthy older adults ( n = 20), and in two clinical groups (acquired dysarthria, n = 15; and developmental dysarthria, n = 19). Analysis indicated that the new subtests were found to be specific and sensitive, valid and reliable, as scores significantly differ between healthy older adults and adults with dysarthria, correlated with other subjective measures of intelligibility, and showed high test–retest reliability. The words and sentences intelligibility subtests can be used to evaluate speech disorders in various populations of Hebrew speakers, thus may be an important addition to the speech–language pathologist's toolbox, for clinical work as well as for research purposes. What this paper adds: What is already known on the subject: 'Dysarthria' is a group of disorders reflecting impairments in the strength, speed and precision of movements required for adequate control of the various speech subsystems. Reduced speech intelligibility is one of the main consequences of all dysarthria subtypes, irrespective of their underlying cause. Indeed, most individuals with dysarthria cope with communicative restrictions due to speech impairments. Thus, language‐sensitive measurements of intelligibility are important in dysarthria assessment. The FDA‐2's words and sentences subtests present standardized and validated tools for the identification of the nature and patterns of oro‐motor movements associated with different types of dysarthria. What this paper adds to existing knowledge: The lack of assessment tools in Hebrew poses challenges to clinical evaluation as well as research purposes. The current study conducted a careful culture‐ and linguistic‐sensitive adaption of the FDA‐2 intelligibility subtests to Hebrew and performed a preliminary validation with relevant clinical populations. First, sets of Hebrew words and sentences were constructed, based on the criteria defined in FDA‐2, as well as on several other factors that may affect performance: emotional valence, arousal and familiarity. Second, the new subtests were validated in healthy older adults ( n = 20), and in two clinical groups (adults with acquired dysarthria, n = 15; and young adults with developmental dysarthria, n = 19). What are the potential or actual clinical implications of this work?: Analyses indicated that the new word and sentence subtests are specific, sensitive, valid and reliable. Namely, (1) they successfully differentiate between healthy individuals and individuals with dysarthria; (2) they correlate with other subjective measures of intelligibility; and (3) they show high test–retest reliability. The words and sentences intelligibility subtests can be used to evaluate speech disorders in various populations of Hebrew speakers. Thus, they may be an important addition to the speech–language pathologist's toolbox, for clinical and research purposes. The methods described here can be emulated for the adaptation of speech assessment tools to other languages.